The role of angling-guides in promoting pro-environmental catch-and-release attitudes and behaviours in the recreational angling community - Farthing, Matthew William (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Angling-guides are respected as opinion leaders of the recreational angling community, but nothing is known of their influence on angler behaviour. Given their social-standing, angling-guides may be perceived as role-models by angling-clients "“ thereby promoting the adoption of best and/or poor catch-and-release (C&R) practices, depending on their individual knowledge, attitudes and behaviour. It is critical to understand their potential influence, their knowledge and their behaviours to inform effective intervention strategies which could exploit their extensive networking potential. The aim of this thesis was to better understand the potential utility of angling-guides in efforts to improve angler behaviour. Firstly, this was done by investigating whether angling-guides are perceived as role-models by angling-clients (Chapter 2). Secondly, it was done by assessing the current level of knowledge, attitudes and behaviours of angling-guides from around the world (Chapter 3). Thirdly, it was done by exploring the relationship between angling-guide knowledge, attitudes, intentions and actual behaviour in a case-study of guided-angling trips (Chapter 4). Lastly, it was done by exploring intervention frameworks and incorporating insights into potential strategies for promoting pro-environmental angling behaviours to angling-guides (Chapter 5). To understand if angling-guides are perceived as role-models by the recreational angling community (Chapter 2), a digital survey was designed to assess previous angling-clients' attitudes towards angling-guides serving the three role-model functions proposed in the Motivational Theory of Role-Modelling, namely as Behavioural models, Representations of the Possible and Inspiration. Of the 492 angling-clients (27 countries), most agreed that angling-guides were competent, skilled, and worth emulating (91.1%), suggesting they are perceived as Behavioural Models. Less agreed that angling-guides were Inspirational or Representations of the Possible (54.8%), suggesting they are less likely to motivate anglers to adopt and/or pursue new goals. As Behavioural Models, angling-guide C&R practices are likely to be emulated, which is of both utility and concern to managers. As angling-guides are likely to be emulated, a digital survey was designed to assess their knowledge, attitudes and behaviours (particularly C&R best-practices) (Chapter 3). Of the 342 angling-guides (47 countries), few had accredited training (9.4%). However, most were deemed "knowledgeable of best-practices" (69.0%), but pervasive misconceptions of key C&R best-practices were observed. Attitudes towards best-practices were generally pro-environmental, and those deemed knowledgeable had significantly more pro-environmental attitudes (p = 0.003). Most angling-guides had pro-environmental attitudes towards their environmental responsibilities (87.1 - 89.5%), but these broad attitudes cannot predict specific pro-environmental behaviours during guided-angling trips where angler satisfaction is often at odds with best-practice. Angling-client satisfaction has important financial implications for angling-guides, and even those with pro-environmental intentions may struggle to adhere to C&R best-practices with inherent sacrifices for the angling-client's enjoyment. Observation of behaviour in context is critical for understanding the behaviour to be changed. To explore the relationship between angling-guide knowledge, intentions and actual behaviour (Chapter 4), five angling-guides were observed (and filmed) interacting with groups of angling-clients during their guided-angling trips over a 30 day period. Five angling behaviours of interest were identified, and a survey focussed on these behaviours was disseminated (18 months later) to the five angling-guides previously observed to assess their knowledge, attitudes, reported behaviours and perceptions of the norm. Generally the subjects' reported behaviours aligned well with their knowledge of best-practice, but their actual behaviour was not well aligned (24.4%). Instead, their actual behaviour aligned better with their perceptions of the norm (80.9%), which was generally a "worse" practice than what they reported. Angling-guides appeared to favour client-satisfaction over pro-environmental behaviour. Gaps between angling-guides' knowledge of best-practice and their actual behaviour indicate that there may be obscure and complex barriers to pro-environmental angling-guide behaviour. Many barriers are seemingly impossible to overcome, such as economic limitations and financial disincentives. These barriers may limit the efficacy of traditional knowledge-attitude-behaviour (KAB) change interventions. The strong alignment of angling-guide behaviour with social norms, and the strong community orientation of recreational angling suggests that the Community-Based Social Marketing (CBSM) approach may be a more effective framework for interventions that aim to promote pro-environmental catch-and-release behaviours at angling-guide level. The CBSM approach allows interventionists to leverage a larger suite of cognitive biases than KAB approaches, provided that sufficient understanding of the context, barriers and benefits for a given segment of the angling-guide community (likely defined by style-of-participation) are obtained. Furthermore, the success of the CBSM approach will depend on the ability of interventionists to effectively recruit and incentivise disjunct and isolated communities of angling-guides to participate in training and workshops in order to achieve the important in-person contact on which the CBSM approach depends.
Keywords: Fishing; Fishing -- Catch effort; Fishing guides; Fishers; Human behavior; Role models